Anatomical Changes in Seedling of Pisum Sativum Linn. Under The Nickel Stress (Indian Journal of Advanced Botany (IJAB), 2024)
A research investigation was conducted to find out how Nickel’s different stresses affected the morphological alterations in Pisum sativum. Pisum sativum has a complex stem structure. In the transactional view, the stem of Pisum sativum is usually more or less square-shaped. The root’s transverse section has a form which is slightly rounded. The structural abnormalities of Pisum sativum treated with different concentrations of Nickel indicated its toxic effect on the anatomical structure of the root and stem. Pisum sativum treated with lower to higher doses of Nickel showed few specific effects on stem anatomy. Plants treated with nickel had many structural changes in their roots.